2020
DOI: 10.3389/fcell.2020.585640
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent Feedforward Regulation via Sox9 and ERK Underpins Mouse Tracheal Cartilage Development

Abstract: Tracheal cartilage provides architectural integrity to the respiratory airway, and defects in this structure during embryonic development cause severe congenital anomalies. Previous genetic studies have revealed genes that are critical for the development of tracheal cartilage. However, it is still unclear how crosstalk between these proteins regulates tracheal cartilage formation. Here we show a core regulatory network underlying murine tracheal chondrogenesis from embryonic day (E) 12.5 to E15.5, by combinin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…One study showed that ERK signaling is required for initial SOX9 activation in primary chondrocytes and C3H10T1/2 cells in vitro [ 30 ] while another noted that ERK activation during late chondrogenic differentiation resulted in increased chondrogenesis in limb bud mesenchyme, but only in the presence of p38/MapK signaling [ 31 ]. Recent studies have identified a unique relationship between ERK signaling and tracheal chondrogenic differentiation, demonstrating the existence of an incoherent feed forward loop where chondrogenesis is activated by SOX9 and simultaneously repressed by ERK [ 32 ]. The role ERK signaling plays during calvarial osteoblast fate decisions is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that ERK signaling is required for initial SOX9 activation in primary chondrocytes and C3H10T1/2 cells in vitro [ 30 ] while another noted that ERK activation during late chondrogenic differentiation resulted in increased chondrogenesis in limb bud mesenchyme, but only in the presence of p38/MapK signaling [ 31 ]. Recent studies have identified a unique relationship between ERK signaling and tracheal chondrogenic differentiation, demonstrating the existence of an incoherent feed forward loop where chondrogenesis is activated by SOX9 and simultaneously repressed by ERK [ 32 ]. The role ERK signaling plays during calvarial osteoblast fate decisions is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic inactivation of either Mek1/2 or Erk1/2 specifically in the airway epithelium results in lung agenesis 19 , implying that ERK and its activation were essential for lung development 20 . Previously, immunofluorescence staining results suggested that the phosphorylation of ERK was most likely to occur in the distal tips of the lung epithelium, and may thus be involved in the budding process during lung development [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…However, in this work we consider the simplified case where incoherent regulation is fed back on to Y itself to give derivative action. Incoherent feedforward motifs are known to be abundant in E. coli and higher organisms [105][106][107][108]. One can speculate that at least some of these motifs are part of feedback circuits, however a rigorous bioinformatic analysis would have to be done to show this.…”
Section: Plos Computational Biologymentioning
confidence: 99%